Enheduana: princess, priestess, poetess - Gadotti, Alhena (Routledge ancient biographies, 2025)
"Enheduana: Princess, Priestess, Poetess offers the first comprehensive biography of Enheduana, daughter of Sargon of Agade and one of the most intriguing, yet elusive, women from antiquity. Royal princess, priestess, and alleged author, Enheduana deserves as much attention as her martial relatives. A crucial contributor in her father's military ambitions, Enheduana nonetheless wielded religious and economic power, as evidenced by primary and secondary sources. Even more interestingly, Enheduana remained alive in the cultural memory of those who came after her, so much so that works attributed to her were integrated in the scribal curriculum centuries after her death. This book aims to situate Enheduana in her own historical context, allowing readers to gain a better understanding of this enigmatic figure, her roles as princess, priestess, and poetess, and the tumultuous times when she lived. This book is suitable for students, scholars, and the general reader interested in the history of the Ancient Near East, ancient literature, and women in the ancient world"-- Provided by publisher